Direct Graft Polymerization of L-lactic Acid onto Oxidatively Functionalized Polypropylene Flakes - Zhang, Zhigang; Zhang, Tianzhu; Ji, Zhenling; Zhou, Xuefeng; Gu, Ning (Asian Journal of Chemistry, 2011)
A facile approach to prepare surface-functionalized polypropylene (PP) with L-lactic acid (LLA) was described. The polypropylene flakes were first treated with an aqueous chromic acid solution and then grafted with L-lactic acid monomer in the aqueous solution. The ATR-FTIR spectroscopy measurements indicate that the existence of carboxylic acid groups (1757 cm-1 for carbonyl; 3350 cm-1 and 1041 cm-1 for hydroxyl in carboxylic acid groups) and morphologies observations by atomic force microscopy show that poly(L-lactic acid) graft covered the surface of polypropylene flake and water contact angle measurements were carried out to monitor the change in hydrophilicity of polypropylene flake surface along the treatment procedure. The cover percentage of poly(L-lactic acid) graft on polypropylene flake is more than 60 %. Poly(L-lactic acid)-grafted polypropylene (PP) (PP-g-PLLA) was eventually obtained with the loss of mechanical property of polypropylene.